METODE FTIR PADA KARAKTERISASI MISELIUM JAMUR TIRAM PUTIH DENGAN BIBIT BERMEDIA SORGUM - Fitriana, Ana; Firdaus, Fitrah Hadi; Nurmaniah, Irlian; Risanti, Maya; Kurniati, Mersi; Irzaman, Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Oyster mushroom’s mycelium was inoculated by sorgum media’s seed were done. FTIR analisys in 400-4000 cm-1 of wave length showed that oyster mushroom’s mycelium possessed of O-H, C-H, C-O, and C=O molecul. O-H molecul showed β-glucan and C-H, C-O, and C=O molecul showed aldehyd, ester, and keton cluster. Keywords: cluster, FTIR, mycelium, oyster mushroom, sorgum.